A Putative Lipid-Associating Motif in the West Nile Virus NS4A Protein Is Required for Efficient Virus Replication - Mikulasova, Andrea; Gillespie, Leah K.; Ambrose, Rebecca L.; Aktepe, Turgut E.; Trenerry, Alice M.; Liebscher, Susann; Mackenzie, Jason M. (Frontiers in Cell and Developmental Biology, 2021)
Flavivirus replication is intimately associated with re-organised cellular membranes. These virus-induced changes in membrane architecture form three distinct membranous “organelles” that have specific functions during the flavivirus life cycle. One of these structures is the replication complex in which the flaviviral RNA is replicated to produce progeny genomes. We have previously observed that this process is strictly dependent on cellular cholesterol. In this study we have identified a putative cholesterol recognition/ interaction amino acid consensus (CRAC) motif within the West Nile virus strain Kunjin virus (WNVKUN) NS4A protein. Site-directed mutagenesis of this motif within a WNVKUN infectious clone severely attenuated virus replication and the capacity of the mutant viruses to form the replication complex. Replication of the mutant viruses also displayed reduced co-localisation with cellular markers recruited to replication sites during wild-type virus replication. In addition, we observed that the mutant viruses were significantly impaired in their ability to remodel cytoplasmic membranes. However, after extensive analysis we are unable to conclusively reveal a role for the CRAC motif in direct cholesterol binding to NS4A, suggesting additional complex lipid-protein and protein-protein interactions. We believe this study highlights the crucial role for this region within NS4A protein in recruitment of cellular and viral proteins to specialised subdomains on membrane platforms to promote efficient virus replication.